The perils of single-sport participation (Changing the games project, 2015)
To be an elite level player at a college or professional sport, you need a degree of exceptional athleticism. And the best medically, scientifically and psychologically recommended way to develop such all around athleticism is ample free play and multiple sport participation as a child.